Genetic diversity analysis of Magnaporthe grisea from some blast nurseries of Hunan province using random amplified polymorphic DNA - Ngueko R B; SHEN Ying; WANG Hong-kai; LIN Fu-cheng; XU Tong (浙江大学学报. 农业与生命科学版)
Diseased samples of Magnaporthe grisea were collected from Anhua, Taojiang, Songbai blast nurseries in Hunan province in 2001. In the previous study the each isolate was characterized by the mating type and Chinese pathotypes. Forty-four isolates tested were analyzed with 13 selected random amplified polymorphic DNA (RAPD) primers in the present work. The isolates tested were classified into 6 different genetic groups (lineages) by UPGMA using the software DPS 2000. Among them lineages Ⅳ and Ⅴ were the predominant one each with 11 isolates while lineage Ⅲ clustered only one isolate. The isolates with Mat 1.1 and Mat 1.2 belonging to different Chinese pathotypes were grouped in the same lineage; moreover isolates of each genetic lineage belonged to different Chinese physiological race. The results obtained confirm the genetic diversity and virulence complexity of rice blast fungus in Hunan province.